How housing burden damages residents’ health: evidence from Chinese cities - Guo, Xiaoxin; Zhong, Shihu; Li, Lin; Luo, Manyi (Frontiers in Public Health, 2024)
Background Currently, China is steadily pursuing high-quality development and promoting common prosperity, for which residents’ health is a precondition. However, high housing-price-to-income ratios and rent-to-income ratios have already triggered many social problems and have substantially affected people’s work and life. It is of practical significance to examine the relationship between housing burden and residents’ health. Methods Combining city-level housing price-to-income ratio data and residents’ health data from the China Family Panel Studies, this study employs a binary logit model to investigate the impact and mechanism of housing burden on residents’ physical and psychological health. Results Overall, a 1% increase in the housing-price-to-income ratio leads to a 1.2% decrease in physical health and a 1.9% decrease in psychological health. In terms of different psychological state indicators, a 1% increase in the housing price-to-income ratio leads to a 1.1% increase in depression, 1.1% increase in nervousness, 1.4% increase in relentlessness, 1.4% increase in hopelessness, 1.0% increase in a sense of incapability, and 1.4% increase in meaninglessness. According to mechanistic analyses, a 1% increase in the housing-price-to-income ratio leads to increases of 0.6 and 0.7% in the smoking rate and late sleep rate, respectively, while it leads to a 0.9% decrease in the noon nap rate. Conclusion A growing housing burden significantly negatively impacts both the physical and psychological health of residents and increases the possibility of negative emotions. Further investigation revealed that the housing burden damages residents’ health by increasing their likelihood of smoking and sleeping late and decreasing their likelihood of taking a nap at noon, while exercise alleviates the negative impacts of the housing burden on residents’ physical and psychological health. Finally, we also find that housing burdens’ impacts on physical and psychological health differ significantly in terms of gender, age, and educational attainment. From the perspective of improving livelihoods, governments should consider the relationship between housing burdens and residents’ health when formulating livelihood policies. Location-specific and targeted policies should be followed. Additionally, efforts should be made to promote exercise among citizens.